A possible genetic factor in the etiology of porphyria turcica - Doğramacı, İhsan; Düzgüneş, Orhan; Ergene, Turhan; Göçmen, Ayhan (The Turkish Journal of Pediatrics, 1962)
Evidence for the existence of a genetic factor in the etiology of porphyria turcica is presented together with a statistical analysis of the probable genetic situation in families with affected children.The comparatively low incidence of the disease in areas where virtually the entire population is known to have been exposed to hexachlorobenzene, the precipitating agent, together with the facts that affected families frequently included more than one member with porphyria and that in several families containing half brothers and sisters the children of one mother escaped while those of the other were affected, are all cited as reasons for concluding that a predisposing factor must exist side by side with the causative, or triggering, factor of hexachlorobenzene ingestion. The nature of the outbreak is such that the historically diverse origins of the local population do not preclude genetic predisposition and are felt to be of comparatively little significance, particularly in view of the large amount of intermarriage and the consequent mingling of genes that has taken place in the region.Evidence from field studies that this disease practically never appears in both parents in affected families despite their common exposure to hexachlorobenzene, indicating a recessive gene, combined with evidence that this form of porphyria is largely confined to children and adolescents, is presented as support for the hypothesis that there is, indeed, a genetic factor involved in porphyria turcica and that in all probability the defect is transmitted by a dominant gene of low penetrance in older persons.